Estructura factorial de la Escala de Autoconcepto Tennessee (Version en Español) - Alfaro-Garcia, Rafael Antonio; Santiago-Negron, Salvador (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Spanish translation, validation and adaptation of the Tennessee Self-Concept Scale (TSCS: Roid & Fitts, I 988/1991/1994), carried out by Rosado (EACT·R: 1992), was used to study the factor structure of this instrument with two populations. The comparative analysis of the adjusted samples was performed with adolescent students (n = 264) and adult employees (n = 544). The EACT-R defined one factor in the Personal Self (both samples). in the Family Self and Self-Criticism (adults) and, in the Physical Self (adolescent,;). The structural validity of the EACT-R was not confirmed by the results obtained in this study. These findings are consistent with previous studies of the TSCS that have not validated its construct nor its multidimensional design.